Extracellular HMGB1 blockade inhibits tumor growth through profoundly remodeling immune microenvironment and enhances checkpoint inhibitor-based immunotherapy - Coraline Radermecker; Pascale Hubert; Patrick Roncarati; Stephanie Demoulin; Charlotte Pilard; Marie Ancion; Celia Reynders; Thomas Lerho; Diane Bruyere; Alizee Lebeau; Margot Meunier; Marie-Julie Nokin; et al. (Journal for ImmunoTherapy of Cancer)
Background High-mobility group box 1 (HMGB1) is a multifunctional redox-sensitive protein involved in various intracellular (eg, chromatin remodeling, transcription, autophagy) and extracellular (inflammation, autoimmunity) processes. Regarding its role in cancer development/progression, paradoxical results exist in the literature and it is still unclear whether HMGB1 mainly acts as an oncogene or a tumor suppressor.Methods HMGB1 expression was first assessed in tissue specimens (n=359) of invasive breast, lung and cervical cancer and the two distinct staining patterns detected (nuclear vs cytoplasmic) were correlated to the secretion profile of malignant cells, patient outcomes and the presence of infiltrating immune cells within tumor microenvironment. Using several orthotopic, syngeneic mouse models of basal-like breast (4T1, 67NR and EpRas) or non-small cell lung (TC-1) cancer, the efficacy of several HMGB1 inhibitors alone and in combination with immune checkpoint blockade antibodies (anti-PD-1/PD-L1) was then investigated. Isolated from retrieved tumors, 14 immune cell (sub)populations as well as the activation status of antigen-presenting cells were extensively analyzed in each condition. Finally, the redox state of HMGB1 in tumor-extruded fluids and the influence of different forms (oxidized, reduced or disulfide) on both dendritic cell (DC) and plasmacytoid DC (pDC) activation were determined.Results Associated with an unfavorable prognosis in human patients, we clearly demonstrated that targeting extracellular HMGB1 elicits a profound remodeling of tumor immune microenvironment for efficient cancer therapy. Indeed, without affecting the global number of (CD45+) immune cells, drastic reductions of monocytic/granulocytic myeloid-derived suppressor cells (MDSC) and regulatory T lymphocytes, a higher M1/M2 ratio of macrophages as well as an increased activation of both DC and pDC were continually observed following HMGB1 inhibition. Moreover, blocking HMGB1 improved the efficacy of anti-PD-1 cancer monoimmunotherapy. We also reported that a significant fraction of HMGB1 encountered within cancer microenvironment (interstitial fluids) is oxidized and, in opposite to its reduced isoform, oxidized HMGB1 acts as a tolerogenic signal in a receptor for advanced glycation endproducts-dependent manner.Conclusion Collectively, we present evidence that extracellular HMGB1 blockade may complement first-generation cancer immunotherapies by remobilizing antitumor immune response.